Effects of Walnut Consumption on Lipid Profile of Female Undergraduate Students - Akbar Ali Babaei (Journal of Fasting and Health, 2019)
Introduction: Cardiovascular disease (CVD) is now an important cause of death all over the world and is a growing health concern. Lifestyle factors, including nutrition, have an undeniable effect on the prevention and treatment of CVD. Walnut has a unique profile and is rich in polyunsaturated fatty acids, which may improve blood lipids and CVD risk factors. Method: A randomized clinical trial, in which 50 participants with a normal lipid profile were randomly divided into two groups. We added 40 gr of walnuts without skin per day for 4 weeks to the usual diet of the intervention group. Results: Paired T-test showed that calorie, protein and fat intake increased significantly in all of the cases, after the consumption of walnuts. At baseline, BMI in control and intervention groups was 21.66 ± 4.06 and 21.22± 4.03 respectively which did not have a significant difference before and after the intervention. We observed a significant decrease in serum LDL and TG concentration in walnut groups after the intervention. Conclusion: The consumption of walnuts could result in decreased serum LDL and TG.